PENERAPAN SOZIALFORMEN DALAM PEMBELAJARAN KETERAMPILAN PRODUKTIV BAHASA JERMAN - Sianturi, Nelli L.; Marantika, Juliaans E. R. (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
The aim of this study is to identify the application of social forms in the process of learning productive skills in the German language and their impact on the learning atmosphere. This research is a descriptive quantitative study. Data was collected through observations and questionnaires. The sample in this study consisted of 16 fourth-semester students of the German Language Education Program.Based on the data collected, it can be concluded that social forms are applied appropriately in the learning process. This was demonstrated by the researcher's observations, which showed that lecturers used various social forms during the lessons. The use of these social forms also influences the classroom learning atmosphere, enabling students to be more active and to interact with one another through this technique.